Atividade antibiofilme de peptídeos sintéticos: mecanismos de ação e aplicações na saúde - Bezerra, Leandro de Paula (2022)
Biofilm-forming yeasts are major public health problem because its high resistance to microbial agents. Among those, Candida albicans, C. krusei and C. parapsilosis are drug-resistant yeasts responsible for bloodstream infections leading individuals to death. To overcome this scenario, synthetic antimicrobial peptides (SAMPs) are considered new weapons to combat infections either alone or conjugated with drugs that are losing their activity because its capacity to cause a disruption of pathogen cell membrane. Here, five SAMPs named Mo-CBP3-PepI, Mo-CBP3-PepII, Mo-CBP3-PepIII, were designed based in the protein sequence of a chitin-binding protein from Moringa oleifera seeds and PepGAT and PepKAA, obtained by a protein sequence from a Arabidopsis thaliana chitinase were tested alone or in combination with Nystatin (NYS) and Itraconazole (ITR) against biofilms formed by C. albicans, C. krusei and C. parapsilosis. Furthermore, the mechanisms behind the antibiofilm activity was evaluated by fluorescence and scanning electron microscopies. The results revealed an improvement of 2 up to 4-fold in NYS and ITR antibiofilm activity when combined with peptides. Microscopic analyses showed that mechanisms of action is based on cell wall degradation, overproduction of reactive oxygen species (ROS) and membrane pore formation causing leakage of internal content and leading biofilm cells to death. By increasing the activity of NYS and ITR, peptides exhibited a great potential as adjuvants. Altogether, results suggest the potential of Mo-CBP3-PepI, Mo-CBP3-PepIII, PepGAT and PepKAA as new drugs and/or adjuvants to increase the activity of conventional drugs for treatment of clinical infection caused by resistant biofilms of Candida specie.